2019
DOI: 10.17221/37/2018-swr
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of microorganisms in metal- and alkali-contaminated soils of Central and North-eastern Slovakia

Abstract: A field-based study and laboratory tests were undertaken to determine the functional diversity of microorganisms in metal- and alkali-contaminated soils in Central and North-eastern Slovakia where iron ore and magnesite have been mined and processed for a long time. To improve the understanding of the functional diversity of microorganisms, we examined the effects of environmental factors on the functional diversity of microorganisms in metal- and alkali-contaminated soils in the emission field of heaps and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…The high soil pH induced by Mg contamination is a major determinant affecting the plant's colonization and growth in this Mg‐contaminated soil (Wang, Zhao, Zeng, Hu, & Yu, ; Yang et al, ). Previous research by Fazekaš, Fazekašová, Adamišin, Huličová, and Benková () demonstrated that the original soil pH value of about five caused by magnesite dust contamination was changed to a pH of about 7.2–8.5. In addition, past research in northern Spain has investigated that the soil pH reaches 9.5 near the magnesite ore calcining plant, and the surface soil pH is most affected (Machín & Navas, ), which was similar to our finding.…”
Section: Discussionmentioning
confidence: 99%
“…The high soil pH induced by Mg contamination is a major determinant affecting the plant's colonization and growth in this Mg‐contaminated soil (Wang, Zhao, Zeng, Hu, & Yu, ; Yang et al, ). Previous research by Fazekaš, Fazekašová, Adamišin, Huličová, and Benková () demonstrated that the original soil pH value of about five caused by magnesite dust contamination was changed to a pH of about 7.2–8.5. In addition, past research in northern Spain has investigated that the soil pH reaches 9.5 near the magnesite ore calcining plant, and the surface soil pH is most affected (Machín & Navas, ), which was similar to our finding.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical stress caused by high concentration of heavy metals affects the number and metabolic activity of microorganisms in soils. High pollution with heavy metals in soils can decrease microbial diversity or disturb functional activity, which may affect nutrient availability for plants [17][18][19]. However, microorganisms that occur in contaminated soils demonstrate the ability to survive in toxic environments through the development of various adaptive mechanisms [20,21].…”
Section: Soil Enzyme Activitiesmentioning
confidence: 99%
“…Currently, only several resistant species are present (Fazekaš et al, 2018). In localities most affected by alkaline dust deposition, the vegetation completely disappeared and a tight, solid Mg-rich, 5-8 mm thick crust was formed on the soil surface, inhibiting the proper soil functioning (Hronec et al, 1992;Fazekaš et al, 2019).…”
Section: Introductionmentioning
confidence: 99%